OCCURRENCE OF PSEUDO-NITZSCHIA SPECIES (BACILLARIOPHYCEAE) AT KUCHING ESTUARIES FROM YEAR 2007 TO 2010 - Lim, Po-Teen (Marine Research in Indonesia, 2012)
Amnesic shellfish poisoning (ASP) is a type of seafood poisoning due to human consumption on shellfish mollusks contaminated with algal toxin, domoic acid (DA) derived from the diatom Pseudo-nitzschia. Bloom dynamics of this diatom in tropical waters were poorly understood due to lack of long term study on the organism. Occurrence of Pseudo-nitzschia species was investigated at Santubong and Samariang estuarine waters, Kuching, Sarawak from 2007 to 2010. The estuaries were characterized by shallow water with semi-diurnal tidal cycle. Cell abundance was determined by microscopic enumeration. Temperature, pH, salinity and macronutrients at the sampling sites were determined at each sampling occasions. Highest cell density of Pseudo-nitzschia spp. was recorded 8.0 Ãâ 103 cells L in Santubong in April 2009 and P. brasiliana cells were found highest in October 2007 (2 Ãâ 104 cells L-1). Increase in cell abundance was coincided with high salinity and low precipitation rate. Water temperature and pH showed insignificant influence on the abundance of Pseudo-nitzschia spp. The result obtained in this study provided fundamental understanding on bloom dynamic of potential harmful Pseudo-nitzschia species in the tropical estuarine waters.